La Stimulation des Échanges Commerciaux Intra-Maghrébins est Subordonné a la Relance du Processus de L'intégration de la Région Maghrébine - Benabderrahmane, Lyes (جامعة عاشور زيان الجلفة - كلية العلوم الاقتصادية والعلوم التجارية وعلوم التسيير, 2022)
Regional economic integration is a powerful catalyst for economic development on which many countries have relied and from which they have realized economic and social dividends. This study aims to analyze the elements of economic integration between the countries of the Arab Maghreb as an approach to broaden the scope of intra-Maghreb and global trade. And through the use of the descriptive method, the absolution of the Maghrebian economic activation represents the appropriate mechanism to promote foreign trade, and for this a certain number of measures must be taken, in particular the coordination of economic policies and legislation. and the establishment of common supra-national institutions.
Keywords: التبادلات التجارية -- التكامل الاقتصادي -- التجارة الخارجية -- المغرب العربي